Development of Calcium Fortified Dog Biscuits incorporated with Chicken Slaughter House Byproducts and Evaluation of its Palatability in Dogs - Virk, Khuspreet Singh; malav, om prakash; Chatli, Manish Kumar; Mehta, Nitin; Kumar, Pavan; Wagh, Rajesh V. (Indian Journal of Animal Nutrition, 2019)
This study was designed to optimize the incorporation level of poultry by-products viz., liver and gizzard along with calcium and selenium fortification for the development of dog biscuits. Poultry liver and gizzard were minced and air dried at 60 Â°C for 15 -16 hrs after that these were converted into powder. Three different levels of poultry liver and gizzard viz., 10%, 20% and 30% were incorporated separately in standardized dog biscuits formulation after replacing the refined wheat flour. All the treatment products were analyzed for sensory evaluation, dog acceptability test, texture profile and instrumental color profile. Incorporation of liver powder at 30% level was found most suitable for the preparation of dog biscuits. The developed product was analyzed for physico-chemical properties (pH and cooking yield), proximate composition (moisture, protein, fat and ash), mineral content (Ca, P and Se), instrumental color and texture profile analysis. The dicalcium phosphate was incorporated at 2% level in the 30% liver powder incorporated dog biscuits with acceptable physico-chemical and sensory qualities.